Urinary Properdin and sC5b-9 Are Independently Associated With Increased Risk for Graft Failure in Renal Transplant Recipients - Lammerts, Rosa G. M.; Eisenga, Michele F.; Alyami, Mohammed; Daha, Mohamed R.; Seelen, Marc A.; Pol, Robert A.; van den Born, Jacob; Sanders, Jan-Stephan; Bakker, Stephan J. L.; Berger, Stefan P. (Frontiers in Immunology, 2019)
Abstract The pathophysiology of late kidney-allograft failure remains complex and poorly understood. Activation of filtered or locally produced complement may contribute to the progression of renal failure through tubular C5b-9 formation. This study aimed to determine urinary properdin and sC5b-9 excretion and assess its association with long-term outcome in renal transplant recipients (RTR). Methods We measured urinary properdin and soluble C5b-9 in a well-defined cross-sectional cohort of RTR. Urinary specimens were taken from the morning urine portion and properdin and sC5b-9 were measured using an enzyme-linked- immunosorbent assay (ELISA). Cox proportional hazard regression analyses were used to investigate prospective associations with death-censored graft failure. Results We included 639 stable RTR at a median [interquartile range] 5.3 (1.8-12.2) years after transplantation. Urinary properdin and sC5b-9 excretion were detectable in 161 (27%) and 102 (17%) RTR respectively, with a median properdin level of 27.6 (8.6-68.1) ng/mL and a median sC5b-9 level of 5.1 (2.8-12.8) ng/mL. In multivariable-adjusted Cox regression analyses, including adjustment for proteinuria, urinary properdin (HR 1.12; 95% CI 1.02-1.28; P=0.008) and sC5b-9 excretion (HR 1.34; 95% CI 1.10-1.63; P=0.003) were associated with an increased risk of graft failure. If both urinary properdin and sC5b-9 were detectable, the risk of graft failure was further increased(HR 3.12; 95% CI 1.69-5.77; P<0.001). Conclusions Our findings point towards a potential role for urinary complement activation in the pathogenesis of chronic allograft failure. Urinary properdin and sC5b-9 might be useful biomarkers for complement activation and chronic kidney allograft deterioration, suggesting a potential role for an alternative pathway blockade in RTR.